PpZAT5 suppresses the expression of a B-box gene PpBBX18 to inhibit anthocyanin biosynthesis in the fruit peel of red pear - Zhang, Lu; Tao, Ruiyan; Wang, Simai; Gao, Yuhao; Wang, Lu; Yang, Shulin; Zhang, Xiao; Yu, Wenjie; Wu, Xinyue; Li, Kunfeng; Ni, Junbei; Teng, Yuanwen; et al. (Frontiers in Plant Science, 2022)
BBX (B-box) proteins play a vital role in light-induced anthocyanin biosynthesis. PpBBX18 was an indispensable regulator for the induction of anthocyanin biosynthesis in the peel of red pear fruit (Pyrus pyrifolia Nakai.). However, the upstream regulation of BBX genes has not been well characterized. In this study, PpZAT5, a cysteine2/histidine2-type transcription factor, was discovered as the upstream negative regulator of PpBBX18. The results showed that PpZAT5 functions as a transcriptional repressor and directly binds to the CAAT motif of PpBBX18 and inhibits its expression. PpZAT5 expression was inhibited by light, which is converse to the expression pattern of anthocyanin-related structural genes. In addition, less anthocyanin accumulated in the PpZAT5-overexpressing pear calli than in the wild type pear calli; on the contrary, more anthocyanin accumulated in PpZAT5-RNAi pear calli. Moreover, the crucial genes involved in light-induced anthocyanin biosynthesis were markedly down-regulated in the transcriptome of PpZAT5 overexpression pear calli compared to wild type. In conclusion, our study indicates that PpBBX18 is negatively regulated by a C2H2-type transcriptional repressor, PpZAT5, which reduces anthocyanin content in pear. The present results demonstrate an upstream molecular mechanism of PpBBX18 and provide insights into light-induced anthocyanin biosynthesis.